Aesthetic Surgical Procedures in Men: Major Complications and Associated Risk Factors. (14th October 2017) - Kaoutzanis, Christodoulos; Winocour, Julian; Yeslev, Max; Gupta, Varun; Asokan, Ishan; Roostaeian, Jason; Grotting, James C; Higdon, K Kye
Abstract: Background: The number of men undergoing cosmetic surgery is increasing in North America. Objectives: To determine the incidence and risk factors of major complications in males undergoing cosmetic surgery, compare the complication profiles between men and women, and identify specific procedures that are associated with higher risk of complications in males. Methods: A prospective cohort of patients undergoing cosmetic surgery between 2008 and 2013 was identified from the CosmetAssure database. Gender specific procedures were excluded. Primary outcome was occurrence of a major complication in males requiring emergency room visit, hospital admission, or reoperation within 30 days of the index operation. Univariate and multivariate analysis evaluated potential risk factors for major complications including age, body mass index (BMI), smoking, diabetes, type of surgical facility, type of procedure, and combined procedures. Results: Of the 129, 007 patients, 54, 927 underwent gender nonspecific procedures, of which 5801 (10.6%) were males. Women showed a higher mean age (46.4 ± 14.1 vs 45.2 ± 16.7 years, P < 0.01). Men had a higher BMI (27.2 ± 4.7 vs 25.7 ± 4.9 kg/m 2, P < 0.01), and were more likely to be smokers (7.1% vs 5.7%, P < 0.01) when compared to women. Men demonstrated similar overall major complication rates compared to women (2.1% vs 2.1%, P = 0.97). When specific complications were analyzed further, men had higher hematoma rates, but lower incidence of surgical site infection. Additionally, major complications after abdominoplasty, facelift surgery, and buttock augmentation were noted to preferentially affect males. On multivariate analysis, independent predictors of major complications in males included BMI (RR 1.05), hospital or ambulatory surgery center procedures (RR 3.47), and combined procedures (RR 2.56). Conclusions: Aesthetic surgery in men is safe with low major complication rates. Modifiable predictors of complications included BMI and combined procedures. Level of Evidence: 2: